Effect of sulfites on the in vitro antioxidant activity of wines - C.D. Di Mattia; A. Piva; M. Martuscelli; D. Mastrocola; G. Sacchetti (Chiriotti Editori, 2015)
The objective of this study was to assess the contribution of SO2 to the overall antioxidant activity of wines. In this study, white, red, and model wines, with increasing sulfite content, were used. The radical scavenging activity of the wines was evaluated by ABTS and DPPH assays, while the reducing capacity of the wines was assessed by the FRAP assay. SO2 positively affected the antioxidant properties of the wines and, in some cases, its contribution to the overall antioxidant activity of wines was higher than that of naturally occurring antioxidants. Depending on the assay, SO2 showed both synergistic and antagonistic effects with the antioxidants naturally present in wines.